Papillary Lesions In The Thyroid Gland - Interesting Facts - Johanes Hadi Lunardhi (JURNAL WIDYA MEDIKA, 2020)
Papillary lesion in the thyroid gland is commonly a malignancy, and they are Papillary Thyroid Carcinoma (PTC)-2,3,4,9. Appropriate diagnosis and treatment of the disease almost demonstrates excellent survival-4,10. On the contrary, there are some other papillary lesions in the thyroid which are not PTC. Benign appearing encapsulated papillary lesion of the thyroid was formerly diagnosed as ‘papillary adenoma’, a benign neoplasm-5,8. If we look back several decades ago, we could find in textbooks the change of opinion that ‘papillary adenoma’ of the thyroid was considered malignant, and no more nomenclature of ‘papillary adenoma’ could be found in pathology textbooks after 19741,7. PTC has many variants in their morphologic presentation. The one interesting is the encapsulated follicular variant of papillary thyroid carcinoma (EFVPTC). This disorder had been treated as cancer for many years. Another change has occured a few years ago. This variant (EFVPTC) has now been proven a non-malignant disease; and a new name has been adopted for, as: non-invasive follicular thyroid neoplasm with papillary-like features (NIFTP); and has to be treated accordingly-6. The morphologic diagnostic features, classification of PTC and its variants, has been presented. Discussion is focused on the ‘encapsulated’ and the ‘follicular’ variants of PTC, to explain the connection on which site the NIFTP and the formerly named ‘papillary adenoma’, should be placed on or may arise from the new classification of thyroid neoplasm. There are other thyroid cancers which produce papillary-like structures, which are not PTC. It is also important to notice some focal papillary fronds/buddings or hyperplasia, found in non-neoplastic thyroid diseases. These changes are delivered briefly on closing this presentation.